2014
DOI: 10.4314/tjpr.v13i9.26
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Applications of Quercetin and its Derivatives: A Short Review

Abstract: Quercetin (3,3ʹ,4ʹ,5,7-pentahydroxyl- flavone) is a flavonol, and it belongs to a class of plant secondary metabolites known as flavonoids. It is present in man's daily diet and is known for biological activities such as antioxidant, antiviral, anticancer, antimicrobial, anti-inflammatory and many more. Quercetin has been reported for its antioxidant and antiviral applications, hence, it is not only used as such but also its various derivatized forms have potentials for development into drugs for the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 42 publications
0
65
0
1
Order By: Relevance
“…They have been shown to exhibit antidiabetic activity [6,7]. They also possess both antidyslipidemic and anti-anemic properties [6].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…They have been shown to exhibit antidiabetic activity [6,7]. They also possess both antidyslipidemic and anti-anemic properties [6].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The level of phytochemicals in the leaf extracts ensured protective roles against oxidative stress associated with hyperglycemia. Flavonoids such as quercetin, boswellic, rutin and ellagic acid have been shown to possess antidiabetic activity [7]. The observed variations in the biological effects of the extracts could be due to variations in the phytochemical constituents [7,8] which in turn might be due to differences in the phytoconstituents of the host plants [18].…”
Section: Data Are Presented As Mean ± Sem (N = 5) A= Extract From Avmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most abundant flavonol, identified in various types of vegetable [19][20][21], caper fruits [22], fruits [23], herbs (dill), some types of tea [24] and wine [25], being of the most extensively studied in this field is the quercetin [11,[26][27][28]. Numerous studies have demonstrated that another plant-origin constituent-curcumin (a yellow substance belonging to the polyphenols superfamily; active component of turmeric, a common Indian spice, derived i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin does have ethnopharmacology property as an anticancer, antioxidant and neuroprotective. Phase-I clinical trials reported inhibition on tyrosine kinase by Quercetin which proposes it's use in tumours 13 .…”
Section: Introductionmentioning
confidence: 99%